Validity of the Teaching Module as a Product of Developing a Problem-Based Learning Model Based on Blended Learning with a Flipped Classroom Approach - Wita Ferwati; Abdul Hasan Saragih; Harun Sitompul (Lembaga Bale Literasi, 2025)
This study aims to develop and determine the validity of a teaching module based on Problem Based Learning (PBL) integrated with a blended learning flipped classroom model in senior high school Biology learning. This research employed a Research and Development (R&D) approach using the Dick and Carey instructional design model, which was limited to the formative evaluation stage through expert validation. The data were collected from four groups of experts, namely instructional design experts, subject matter experts, media experts, and language experts. The research instrument used was a Likert-scale validation sheet, and the data were analyzed using descriptive quantitative analysis techniques. The results revealed that the developed teaching module was categorized as feasible across all assessed aspects. Instructional design validation obtained 85.67%, subject matter validation 84.33%, media validation 80.16%, and language validation 82.78%. Overall, the teaching module is considered feasible for use in senior high school Biology learning, although minor revisions are still required, particularly in the media aspect. This module is expected to support student-centered learning, enhance conceptual understanding, and improve students’ higher-order thinking skills through the integration of PBL and the flipped classroom model.